(untitled) (Homoeopathy for All, 2022)
Gastro-oesophageal reflux resulting in heartburn affects approximately 30% of the general population.2 Occasional episodes of gastro oesophageal reflux are common in healthy individuals. Reflux is normally followed by oesophageal peristaltic waves that efficiently clear the gullet, alkaline salivane utralises residual acid and symptoms do not occur. Indigestion is a nonspecific term that encompasses a variety of upper abdominal complaints including heartburn, regurgitation, and dyspepsia (upper abdominal discomfort or pain). These symptoms are overwhelmingly due to gastro esophageal reflux disease (GERD).1